Two-level optimal scheduling method for a renewable microgrid considering charging performances of heat pump with thermal storages. (February 2023) - Liu, Fang; Mo, Qiu; Zhao, Xudong
Abstract: Combining compression heat pump with thermal energy storage (HPTES) allows the shifting of heat demand to off peak periods or periods with surplus renewable electricity. However, it is not clear that how the charging performances (efficiency, charging time and supply water temperature) of HPTES affect the optimal coordinated scheduling of a renewable microgrid. In this study, we proposed a two-level scheduling optimization method for a renewable grid-connected microgrid considering charging performances of heat pump with thermal storages. This method is based on an integrated nonlinear dynamic model of a renewable microgrid including photovoltaic/wind power generator, buildings and HPTES; and the time lag in energy conversion and transport process was considered. Level I in this method is for the scheduling optimization of HPTES, three different model-based dynamic optimal control strategies were developed for the charging process of HPTES to supply domestic hot water and floor radiant heating in buildings. It's found that coefficient of performance (COP) of HPTES during charging varies with the charging time and the supply water temperature. Thus at the level II, a half-hourly time interval was proposed for the optimal scheduling of microgrid, through which a hybrid charging time scheduling can be applied to the optimal control of HPTES for different supply water temperatures. Based on the microgrid model integrating different optimal control strategies of HPTES, different dynamic optimal coordinated scheduling were developed for the microgrid in three scenarios. It can be found that the charging performances of HPTES affect the optimal coordinated scheduling of heat supplies from heat pump and TES in a microgrid significantly, and heat production rates vary with time differently under different operation scheduling of a microgrid. The proposed optimal half-hourly scheduling method with hybrid charging time of HPTES leads to the reduction of the overall operating cost including the penalty cost for the microgrid, and the increase of domestic hot water temperature up to the required value. This study would be useful for the optimal scheduling of a renewable microgrid containing HPTES at a low cost in practice.